한국의 핵비확산 외교와 원자력정책 - 이상현; Sang Hyun Lee (한국과 국제정치, 2011)
한국은 북핵문제와의 연관성 속에 원자력의 평화적 이용을 확대해 나가면서도 핵무기 없는 세상을 만드는 모범적인 국가로서의 위상을 굳건히 하고, 미래 원전기술 및 안전기술 개발을 통해 인류의 발전에 기여하는 국가로서의 정체성을 확립하는 것을 비확산 외교의 목표로 삼아야 한다. 미국의 NPR이나 핵안보정상회의는 강화되는 국제사회의 핵비확산 추세를 잘 보여준다. 한국은 에너지 부족국가로서 원자력의 이용·개발을 확대해야 한다. 하지만 북핵위기가 지속되고 있고, 2014년 만료되는 한미 원자력협력협정을 개정해야 하는 중요한 외교적 과제를 앞두고 있다. 한국의 과제는 첫째, 비확산 문제의 성실한 관리자로서 제2차 핵안보정상회의 등 국제적으로 비확산 준수의 평판을 제고시킬 기회를 적극 활용해야 한다. 둘째, 국제 핵비확산 신뢰성 확보를 위한 노력을 배가해야 한다. 국가적으로 핵비확산 의지를 지속적으로 천명하는 한편, 정부가 비확산 문화의 확산을 계도 및 선도해야 한다. 셋째, 한국 원자력 외교의 강화가 시급하다. 넷째, 핵비확산 및 원자력 이용·개발의 국제적 추세를 정확히 진단하고 우리의 대응전략을 수립하려는 노력을 강화해야 한다. 특히 한국의 원자력정책이 미국의 원자력정책과 가급적 합치되도록 하는 것이 중요하다. 다섯째, 마지막으로 우리의 원전 수출 경쟁력을 강화하는 데 주력해야 한다. South Korea should pursue a strong nuclear non-proliferation policy as well as safe and credible policy of peaceful use of nuclear energy. Recent trends show that international requirements for nuclear non-proliferation are getting tougher, including U.S. non-proliferation policies. South Korea, as a country with severe energy shortage, must expand its use of nuclear energy. However, North Korean nuclear crisis continues to pose threats to such endeavors. And South Korea should renegotiate the Korea-U.S. Nuclear Cooperation Agreement which expires in 2014. First, South Korea should take opportunities such as Second Nuclear Security Summit to raise its reputation as a strong proponent of nuclear non-proliferation. Second, South Korea should strengthen its efforts to acquire international community`s confidence on its compliance credibility. Third, South Korea should enhance its nuclear diplomacy vis-a-vis international community. Fourth, South Korea should formulate national nuclear strategies that correspond to international trends in non-proliferation and peaceful use of nuclear energy. In particular, it is critically important to coordinate South Korea`s nuclear policy with that of the United States. Fifth and finally, South Korean government must support its nuclear industries to get competitive edge in international nuclear energy market.